فاعلية استخدام إستراتيجية التدريس القائم على الاستبطان في تنمية المفاهيم العلمية لدى تلاميذ الصف الرابع الأساسي في مادة العلوم - الدبسي, أحمد; العلان, سوسن (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف البحث إلى تعرّف فاعلية استخدام إستراتيجية التدريس القائم على الاستبطان في تنمية المفاهيم العلمية لدى تلاميذ الصف الرابع الأساسي في مادة العلوم من خلال الإجابة على التساؤل الرئيسي الآتي : ما فاعلية استخدام استراتيجية التدريس القائم على الاستبطان في تنمية المفاهيم العلمية لدى تلاميذ الصف الرابع الأساسي في مادة العلوم اعتمد البحث على المنهج التجريبي لكشف أثر استخدام إستراتيجية التعلّم القائم على الاستبطان في تنمية المفاهيم العلمية لدى تلاميذ الصف الرابع الأساسي. تكون مجتمع البحث من جميع تلاميذ الصف الرابع الأساسي في منطقة النشابية التابعة لمديرية تربية ريف دمشق والمكوّن من 250 تلميذاً وتلميذة أُختير منهم بالطريقة القصدية (92) تلميذاً بوصفهم عينة ضابطة وتجريبية. توصل البحث إلى النتائج الآتية: - وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0.01) بين متوسطي درجات تلاميذ المجموعة التجريبية والمجموعة الضابطة في التطبيق البعدي للاختبار. - وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0.01) بين متوسطي درجات تلاميذ المجموعة التجريبية والمجموعة الضابطة في التطبيق البعدي المؤجل للإختبار - وجود فروق ذات دلالة إحصائية عند مستوى دلالة (0.01) بين متوسطي درجات تلاميذ المجموعة التجريبية والمجموعة الضابطة في التطبيق القبلي للإختبار, من أجل حساب تكافؤ المجموعات فقط . وخلص البحث إلى المقترحات الآتية: - إقامة دورات تدريبية مستمرة لتاهيل المعلمين على استراتيجيات التدريس العقلية. - إجراء دراسات تتناول فاعلية هذه الإستراتيجية في بقية المواد الدراسية. The research aims at identifying the effective use of teaching strategy, based on introspection in the development of scientific concepts in the fourth-grade students in science by answering the main question as follows: The effective use of teaching strategy based on introspection in the development of scientific concepts to students in the fourth-grade science Research was based on the experimental method to detect the impact of the use of learning strategy based on introspection in the development of scientific concepts to students of fourth-grade. Be the research community from all fourth-grade students in the Alnhabbip of the Directorate of Education Damascus Province, consisting of 250 male and female pupils that were chosen in the manner intentional (92) as students sample officer and pilot. Search to find the following results: - The presence of statistically significant differences at the level of significance (0.01) between the mean scores of pupils in the experimental group and control group in the post application of the test. - The presence of statistically significant differences at the level of significance (0.01) between the mean scores of pupils in the experimental group and control group in the post application deferred for testing - The presence of statistically significant differences at the level of significance (0.01) between the mean scores of pupils in the experimental group and control group in the pre-application for the test to calculate the reward groups only. The research concluded the following proposals: - Training courses for continuing training of teachers on strategies for teaching mental - Conduct studies on the effectiveness of this strategy in the rest of the subjects.